2015
DOI: 10.18844/cjes.v1i1.65
|View full text |Cite
|
Sign up to set email alerts
|

Academic performance of Students during transition period before choice of disciplines in Nigeria Certificate in Education (Technical) programme

Abstract: The study examined the academic performance of students in the compulsory courses in technical education during the transition period of first and second years of three years Nigeria Certificate in Education (NCE) Technical programme before choosing their disciplines in the third year. The study comprised of 237 students that consisted of Automobile, 22; Building, 8; Electrical/Electronics, 21; Metalwork, 24; and Woodwork, 4 admitted into year one in 2002/2003, 2003/2004 and 2004/2005 academic sessions who tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, for those with poor performance the aftermath may include expulsion, academic probation, changing of current course of study, academic insecurity during their course of study and low self-esteem. Amasuomo (2015) quoting Universities Admission Center reported that "tertiary institutions in Austria have found that all the academic achievements of an undergraduate are the best single predictors of tertiary success for most tertiary courses" p.195. The most widely used term for undergraduates' academic achievement is their Grade Points Average (GPA) or Cumulative Grade Points Average (CGPA); it is also the "yardstick" used to measure the academic achievements and output of students, teachers, and the university.…”
Section: Academic Achievements Among University Undergraduatesmentioning
confidence: 99%
“…However, for those with poor performance the aftermath may include expulsion, academic probation, changing of current course of study, academic insecurity during their course of study and low self-esteem. Amasuomo (2015) quoting Universities Admission Center reported that "tertiary institutions in Austria have found that all the academic achievements of an undergraduate are the best single predictors of tertiary success for most tertiary courses" p.195. The most widely used term for undergraduates' academic achievement is their Grade Points Average (GPA) or Cumulative Grade Points Average (CGPA); it is also the "yardstick" used to measure the academic achievements and output of students, teachers, and the university.…”
Section: Academic Achievements Among University Undergraduatesmentioning
confidence: 99%